Acessibilidade em ambientes virtuais de aprendizagem: possibilidades para estudantes com deficiência visual - Siqueira, Ana Lucia Farão Carneiro de (2017)
This dissertation was developed in the Master's Program in Education, in the research's line of Pedagogical Formation and Practice of Professional Teacher, from the University of Western Sao Paulo. The research aims to analyze the resources needed so that virtual learning environments can enable accessibility, autonomy and independence for students with visual impairment. This research adopts a qualitative approach. The study was carried out at a Public Higher Education Institution (HEI), located in the state of Sao Paulo, Brazil, which has been offering distance education courses since 2009, period in which was set up its Distance Education Center (known as NEaD). In this context, the Virtual Learning Environment (VLE) used by this HEI in the offer of courses in distance learning was analyzed. In addition to the analysis of this VLE, with the purpose of enriching the data and analyzes carried out, as well as to identify the level of accessibility of the learning environment and resources available, this study considered the participation of two subjects, that is, two Students Target Audience of Special Education (known as EPAEE) with visual impairment. The following instruments were used to collect data: observation and semi-structured interview. Researchers such as Moran, Santarosa, Sonza, Schlünzen, Trentin, Valente among others were studied in order to address aspects related to accessibility and technologies. Based on data gathered from the researcher's observation, added to information obtained with the invited participants and the theoretical basis studied, it was possible to present indicators needed for the inclusion of people with visual impairment in VLE in online courses, understanding which changes HEIs should trigger to adjust the attendance to these people